1981
DOI: 10.1677/joe.0.0880271
|View full text |Cite
|
Sign up to set email alerts
|

Independent Down-Regulation of Insulin and Calcitonin Receptors on a Human Tumour Cell Line

Abstract: A human lung cancer cell line (BEN cells) with a calcitonin receptor and calcitonin-responsive adenylate cyclase also possesses an insulin receptor. This has been characterized and found to have properties similar to those of other mammalian cell insulin receptors. A receptor number of 58 000 per cell was calculated from curvilinear Scatchard plots, and dissociation of bound labelled insulin by dilution was facilitated by the addition of unlabelled insulin, consistent with negatively co-operative interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
(30 reference statements)
3
12
0
Order By: Relevance
“…These results are concordant with earlier observations, which demonstrated that 'irreversibility' of 125 I-sCT binding was independent of the system of assay, occurring in whole cells (Findlay et al 1981, Chao & Forte 1983, membranes (Fischer et al 1981, Nicholson et al 1988b) and solubilised receptor (Nicholson et al 1988a) preparations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are concordant with earlier observations, which demonstrated that 'irreversibility' of 125 I-sCT binding was independent of the system of assay, occurring in whole cells (Findlay et al 1981, Chao & Forte 1983, membranes (Fischer et al 1981, Nicholson et al 1988b) and solubilised receptor (Nicholson et al 1988a) preparations.…”
Section: Discussionsupporting
confidence: 92%
“…In virtually all the systems studied, the binding of 125 I-sCT to its receptor has been essentially irreversible. This is true of human or rat tissue membrane preparations (Fischer et al 1981, Nicholson et al 1988b, as well as clonal cell lines of rat or human origin (Findlay et al 1981, Chao & Forte 1983. Poor reversibility is also maintained in solubilised receptor preparations (Nicholson et al 1988a).…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of CT receptors also been reported in mouse calvariae, human carcinoma cell lines, and rat kidney cells (34,(36)(37)(38), and internalization of CTR and necessity of new protein synthesis for new receptor formation has been reported in a human breast cancer cell line (36). However, the "escape phenomenon" cannot be explained solely on receptor internalization, because many other receptors such as the insulin receptor also are internalized (38), and forskolin, an adenylate cyclase activator, induced similar effects in osteoclasts, including the "escape phenomenon" and inhibition of bone resorption (39).…”
Section: Discussionmentioning
confidence: 75%
“…In other work, using immunocytochemical methods, we have shown that calcitonin treatment of rat osteoclasts is associated with an increase in cy- The present work provides a basis for studying its significance, besides offering a means of studying directly in osteoclasts some particular features of calcitonin action which might be related to its therapeutic use. These include the phenomena of calcitonin-induced receptor loss (43,44), "escape" (45), persistent activation of adenylate cyclase (12, 46), and homologous desensitization (12, 43).…”
Section: Discussionmentioning
confidence: 99%